2022
DOI: 10.1371/journal.pone.0278595
|View full text |Cite
|
Sign up to set email alerts
|

Time to positivity of Corynebacterium in blood culture: Characteristics and diagnostic performance

Abstract: The presence of Corynebacterium in blood samples can indicate true bacteremia or contamination, thus complicating the diagnosis of true bacteremia. We aimed to evaluate the usefulness of time to positivity (TTP) in diagnosing true bacteremia and contamination in cases where Corynebacterium was isolated from blood samples. We compared the TTP of the true-bacteremia group (n = 77) with that of the contamination group (n = 88). For the true-bacteremia cases that had only one set of positive blood cultures (n = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, we observed that the time to blood culture positivity (27h on average). In previous researches, a 13 cases of C. striatum-BSI show this result was 26.7h and a 77 cases of study on Corynebacterium was 26.8h 14,17 . However, it was longer compared to MRSA (20h) and MRSE (19h).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our study, we observed that the time to blood culture positivity (27h on average). In previous researches, a 13 cases of C. striatum-BSI show this result was 26.7h and a 77 cases of study on Corynebacterium was 26.8h 14,17 . However, it was longer compared to MRSA (20h) and MRSE (19h).…”
Section: Discussionmentioning
confidence: 86%
“…Corynebacterium striatum is commonly implicated as a contaminant in bloodstream infections, with literature reporting contamination rates ranging from 29% to 42% 5,17,18 . Differences in these rates primarily stem from varying criteria used to ascertain contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The human gut microbiome is a topic of intense research interest and many bacterial species have been associated with specific diseases 1 . One such species is Ruminococcus gnavus, for which associations with human health have been reported in the context of various ailments [2][3][4][5][6][7] . Officially, its taxonomic status has been revised and R. gnavus is now member of the genus Mediterraneibacter 8 .…”
Section: Introductionmentioning
confidence: 99%